Mobile Application Design: Sale of Clothes Through Electronic Commerce - Jauregui-Velarde, Raul (2022)
“During the COVID-19 pandemic, small clothing sales companies lost economic income and customers due to a lack of digital transformation, causing the dismissal of many employees. Due to this problem, our objective is to design an ecommerce mobile application for the sale of clothes, so that Small and medium-sized enterprises dedicated to this area generate income and retain their customers. For this, the Rational Unified Process (RUP) methodology was applied, because this methodology provides a structured way for companies or developers to visualize the development of the software, and for the validation by expert judgment, the survey and the questionnaire were used as instruments. Obtaining as a result a positive rating for the design of the mobile application and its acceptance to accommodate what is reflected. In conclusion, the e-commerce mobile application was successfully designed, backed by expert judgment, so that Small and medium-sized enterprises can offer their products and generate income, as well as build customer loyalty. “